The life of an environmental strategist : an observation study from an environmental communicator’s perspective - Jaensson, Stina (SLU/Dept. of Urban and Rural Development, 2009)
This thesis is based on an internship at Södertälje Municipality. During three weeks I have observed and interviewed the environmental strategists in order to understand their view on communication. I have also dug deeper into one of the projects to get a better understanding of their work. Most of the strategists’ out-turning projects are based on a classical communication model where the focus is on the sender and on the messages they want to deliver. This model does not take the receivers perspective into account and is therefore difficult to use when trying to changes people’s behavior. According to for example McKenzie-Mohr and Nitsch, it is important with communication in order to make a change and take the target group’s perspective. During my time in Södertälje I have realized that there are several barriers for not communicating. Time constrains, resources and lack of knowledge are some factors which make this work difficult. With some more efforts on communication in the environmental strategists’ work in Södertälje they can though be able to take others perspectives, get feedback and hopefully give people the tools to change behavior and act in a more sustainable way.